High‐Rate Performance of Fluorinated Carbon Material Doped by Phosphorus Species for Lithium‐Fluorinated Carbon Battery. Issue 6 (27th April 2022) - Zhu, Delun; Yuan, Jingchao; Dai, Yang; Peng, Yuqing; Li, Wenrong; Zhang, Fangzhou; Li, Aijun; Zhang, Jiujun
Abstract : The lithium–fluorinated carbon (Li/CF x ) battery possesses the highest energy density (2180 Wh kg −1 ) among all the primary lithium batteries. However, the poor electronic conductivity of the fluorinated carbon (CF x ) material sets a limit on its rate discharge capability, confining its practical application. In this article, a doping strategy at a mild anneal condition is developed to synthesize the phosphorus species‐doped CF x materials (P‐CF x ) for Li/CF x batteries. Compared to the commonly used methods, this eco‐friendly, and simple doping method does not involve washing, centrifugation, and filtration processes. Characterization using X‐Ray diffraction, high‐resolution transmission electron microscope, and X‐Ray photoelectron spectroscopy confirms the successful doping and the structure of the P‐CF x . Density functional theory calculations and characterization results demonstrate that phosphorus species doping can alter microstructure and induce charge redistribution to improve electronic and ionic conductivity. Therefore, the Li/P‐CF x battery possesses a high specific capacity and an excellent rate capability, shown by a high discharge capacity of 810 mAh g −1 with a voltage plateau of 2.53 V at 0.1 C. Extraordinarily, a discharge capacity of 597 mAh g −1 with a voltage plateau of 1.90 V at 20 C has been achieved as well as a high power density of 34 048 W kg −1 . Abstract : An effective and eco‐friendly phosphorus species doping method is developed to modify the fluorinated carbon (CF x ) cathode material. The phosphorus species doping (P‐doping) can alter microstructure and induce charge redistribution to improve capacity and rate performance. The Li/P‐doping‐CF x battery achieves a specific capacity of 597 mAh g −1 and a high power density of up to 34 048 W kg −1 at 20 C.